Tertiary Students' Deficiency in English Emphatic Listening Skills of NLP Matching and Mirroring Technique - Rita Hartati; Meisuri; Siti Aisyah Ginting; Ariatna (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2023)
Active Empathic listening is an activity that combines traditional active listening procedures with the element of empathy, which will result in a higher form of listening (Drollinger, Comes & Warrington, 2006, p.162). Drollinger et al. conceptualized AEL (active empathic listening) as a three-stage activity: sensing, processing, and responding. Empathic listening helps us to listen and understand how others feel. It is one of the most essential social skills we need to maintain healthy relationships with others. Empathic listening helps us to relate to those around us more healthily and effectively. Empathic listening helps to get into a conversation, especially with college students. This research will use a Google form as a questionnaire instrument filled out by participants. The research reveals that participants rarely heard about Empathic Listening and used it in conversation because it was never heard and learned before; some say it is not interesting to learn.